2019
DOI: 10.1038/s41598-019-42302-x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory shear potentiates latent TGF-β1 activation more than steady shear as demonstrated by a novel force generator

Abstract: Cardiovascular mechanical stresses trigger physiological and pathological cellular reactions including secretion of Transforming Growth Factor β1 ubiquitously in a latent form (LTGF-β1). While complex shear stresses can activate LTGF-β1, the mechanisms underlying LTGF-β1 activation remain unclear. We hypothesized that different types of shear stress differentially activate LTGF-β1. We designed a custom-built cone-and-plate device to generate steady shear (SS) forces, which are physiologic, or oscillatory shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Among the mechanosensitive mechanisms controlling TGFβ family signaling is integrin‐dependent activation of latent TGFβ ligand 52 . While FSS has been shown to activate latent TGFβ through a mechanism sensitive to FSS magnitude and flow profile (steady vs oscillatory 17 ), we find that FSS stimulates Smad phosphorylation even with saturating levels of active TGFβ ligand. This suggests that mechanoactivation of latent TGFβ is not the sole mechanism through which FSS targets this pathway in osteocytes.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Among the mechanosensitive mechanisms controlling TGFβ family signaling is integrin‐dependent activation of latent TGFβ ligand 52 . While FSS has been shown to activate latent TGFβ through a mechanism sensitive to FSS magnitude and flow profile (steady vs oscillatory 17 ), we find that FSS stimulates Smad phosphorylation even with saturating levels of active TGFβ ligand. This suggests that mechanoactivation of latent TGFβ is not the sole mechanism through which FSS targets this pathway in osteocytes.…”
Section: Discussionmentioning
confidence: 59%
“…Kunnen et al report that FSS‐mediated activation of TGFβ signaling is blocked in cells treated with the ALK4/5/7 inhibitor LY‐364947, and also observed mild decreases of active and total TGFβ1 levels in flow media following application of FSS 16 . On the contrary, Kouzbari et al and Albro et al showed that levels of active TGFβ1 in platelet releasates and synovial fluid, respectively, increase after stimulation with FSS 17,18 . As a result, the extent to which this mechanism depends primarily on ligand‐level, receptor‐level, or downstream regulation in a cell type‐specific manner remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Oscillation of the shear stress on the vascular endothelial cells has been noted in the pathogenesis of vascular dilation through activation of inflammatory signals [ 74 , 92 97 ]. Compared with physiological steady shear stress, oscillatory shear stress induces higher activation of TGF-β1 which drives pathological vascular remodelling [ 94 ]. Endothelial cilia dysfunction contributes to aberrant fluid-sensing and thus results in vascular disorders, such as aneurysm formation and atherosclerosis [ 98 , 99 ] Therefore, increased oscillatory shear stress due to reciprocating CSF movements may directly activate flow-mediated dilation at the cerebral aqueduct, and it may generate a synergistic effect of increased stroke volumes at the nearby upstream CSF pathways in the ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…As cellular functions often depend on cellular shape and orientation, which are determined by flow-induced hemodynamics, effort has been made to model complex blood flow observed in in vivo settings. Atheroprone oscillatory flow can be induced using the cone and plate shear devices [ 40 ] or parallel plate flow chambers [ 41 ]. Sinha et al [ 42 ] have developed a medium-throughput cell culture device that can produce variously oriented anisotropic biaxial strains by stretching a cell-growing surface membrane, which models strains caused by vascular wall changes in shape and mechanical properties, as seen in various vascular diseases, such as atherosclerosis.…”
Section: In Vitro Systems To Model Flow Dynamics and Endothelial Wall Shear Stress (Wss)mentioning
confidence: 99%